2019
DOI: 10.1016/j.molcel.2019.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Small RNA Sequencing Unravels the Molecular Principles of MicroRNA Homeostasis

Abstract: Argonaute-bound microRNAs silence mRNA expression in a dynamic and regulated manner to control organismal development, physiology, and disease. We employed metabolic small RNA sequencing for a comprehensive view on intracellular microRNA kinetics in Drosophila. Based on absolute rate of biogenesis and decay, microRNAs rank among the fastest produced and longest-lived cellular transcripts, disposing up to 10 5 copies per cell at steady-state. Mature microRNAs are produced within minutes, revealing tight intrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
157
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(165 citation statements)
references
References 82 publications
(112 reference statements)
6
157
0
2
Order By: Relevance
“…This model well explains the strand ratio assessed by next generation sequencing and the magnitudes of target repression by each strand obtained from reporter assays, as recently confirmed by another group [59]. Importantly, a recent time-resolved small RNA sequencing study using thiol (SH)-linked alkylation for the metabolic sequencing of RNA (SLAM-seq) has provided a quantitative view of miRNA production and destruction in Drosophila S2 cells ( Figure 2c) [60]. The processing of pri-miRNAs and pre-miRNAs and generation of miRNA duplexes occurs in a matter of seconds or minutes, more rapidly than the generation of most mRNAs, and loading onto Ago proteins occurs approximately 1 h after the start of biogenesis, suggesting that Ago loading is a key bottleneck step for ensuring faithful miRNA production.…”
Section: Quantitative Features Of Mirna Biogenesis and Functionsupporting
confidence: 76%
“…This model well explains the strand ratio assessed by next generation sequencing and the magnitudes of target repression by each strand obtained from reporter assays, as recently confirmed by another group [59]. Importantly, a recent time-resolved small RNA sequencing study using thiol (SH)-linked alkylation for the metabolic sequencing of RNA (SLAM-seq) has provided a quantitative view of miRNA production and destruction in Drosophila S2 cells ( Figure 2c) [60]. The processing of pri-miRNAs and pre-miRNAs and generation of miRNA duplexes occurs in a matter of seconds or minutes, more rapidly than the generation of most mRNAs, and loading onto Ago proteins occurs approximately 1 h after the start of biogenesis, suggesting that Ago loading is a key bottleneck step for ensuring faithful miRNA production.…”
Section: Quantitative Features Of Mirna Biogenesis and Functionsupporting
confidence: 76%
“…These findings suggest that mosquito Nbr may trim pre-piRNAs generated through a Zuc-mediated endonucleolytic cut, but that only a minor fraction of such pre-piRNAs undergo trimming. Nbr-mediated trimming may be a general hallmark of aging piRNAs, as has recently been proposed for miRNAs (47). aegypti, a clear mosquito ortholog of PARN-1 can be identified: AAEL001426.…”
Section: A Subset Of Responder Pirnas Undergoes Nibbler-mediated Trimmentioning
confidence: 83%
“…miRNAs are found in the plasma and serum encapsulated in extracellular vesicles or bound with special lipid proteins, which make them resistant to RNase digestions ( 26 ). Several lines of evidence reported that these miRNAs have faster biogenesis and activation rates, and longer half-lives relative to mRNA and proteins, which make them suitable for detection at early stages (diagnostic), during progression or treatment selection (prognostic) ( 27 , 28 ). One of the pitfalls of using single circulatory miRNA is the lack of specificity.…”
Section: Aberrant Expression Of Mirnas: Potential Diagnostic and Progmentioning
confidence: 99%